NAD+ Homeostasis and NAD+-Consuming Enzymes: Implications for Vascular Health - Roberto Campagna; Arianna Vignini (MDPI AG, 2023)
Nicotinamide adenine dinucleotide (NAD+) is a ubiquitous metabolite that takes part in many key redox reactions. NAD+ biosynthesis and NAD+-consuming enzymes have been attracting markedly increasing interest since they have been demonstrated to be involved in several crucial biological pathways, impacting genes transcription, cellular signaling, and cell cycle regulation. As a consequence, many pathological conditions are associated with an impairment of intracellular NAD+ levels, directly or indirectly, which include cardiovascular diseases, obesity, neurodegenerative diseases, cancer, and aging. In this review, we describe the general pathways involved in the NAD+ biosynthesis starting from the different precursors, analyzing the actual state-of-art of the administration of NAD+ precursors or blocking NAD+-dependent enzymes as strategies to increase the intracellular NAD+ levels or to counteract the decline in NAD+ levels associated with ageing. Subsequently, we focus on the disease-related and age-related alterations of NAD+ homeostasis and NAD+-dependent enzymes in endothelium and the consequent vascular dysfunction, which significantly contributes to a wide group of pathological disorders.